US-China Economic and Political Competition: Impact on Global Change (Conferencea, 2023)
The increasing economic and political competition between the United States and China is a defining feature of the 21st century, with profound implications for the global order. This article examines the multifaceted nature of this rivalry, exploring its impact on global trade, finance, security, and governance. We argue that while economic interdependence has created incentives for cooperation, the pursuit of national interests and ideological differences has fueled strategic competition. The article analyzes the key areas of competition, including trade wars, technological decoupling, and vying for influence in international institutions. We highlight how this rivalry is reshaping global value chains, accelerating technological innovation, and leading to a bifurcation of global governance structures. Furthermore, we examine the impact on developing countries, many of which face pressure to choose sides or navigate a multipolar world. The article concludes by discussing potential scenarios for the future of US-China relations and their implications for global stability and prosperity. We argue that managing this rivalry effectively is crucial for mitigating risks and fostering a more cooperative and inclusive international order.